Similarities and Differences of Euphemisms in the English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Throughout our lives, we come across euphemisms several times. When we read a novel or in the composition of stories and poems, we encounter such words. They are often considered negative words and are aimed at conveying negative meanings. For this reason, they are used in order to increase the realization of the situations written in the story or work, to convey that situation to the reader. Each language has euphemisms that are connected with its culture, traditions and history. Such words change and are used depending on the ethnic grouping and formation of the language. Euphemisms are not just formed, they are formed depending on the social use and history of the language and remain in the word-stock of the language. This article analyzes the similarities and differences of euphemisms in English and Uzbek languages. Since the stages of development and cultural aspects of two languages are different, the occurrence and use of euphemisms in them are also varied.